Vibrational Stability of NLC Linac accelerating structure - Pimpec, F; Adiga, S; Asiri, F; Bowden, G; Doyle, E; McKee, B; Seryi, A; Redaelli, S (2002)
The vibration of components of the NLC linac, such as accelerating structures and girders, is being studied both experimentally and analytically. Various effects are being considered including structural resonances and vibration caused by cooling water in the accelerating structure. This paper reports the status of ongoing work.